Costa Rica : Five Years after CAFTA-DR, Assessing Early Results for the Costa Rican Economy - World Bank (Washington, DC, 2014)
The Dominican Republic - Central America - United States Free Trade Agreement (CAFTA-DR) has been fundamental in creating a stable framework for Costa Rica's trade with the United States. For Costa Rica, CAFTA-DR is more than a trade agreement. Besides eliminating tariffs and reducing non-tariff barriers between member countries, CAFTA-DR also introduced major changes to the legal framework of member countries, reducing barriers to services, promoting transparency, and ensuring a secure and predictable environment for investors. This report analyses how CAFTA-DR has impacted the Costa Rican economy in the five years after ratification, both on a macro level and in key specific sectors. The report shows that CAFTA-DR is yielding benefits to the Costa Rican economy, but it is too early to provide a complete account just after five years. The agreement has succeeded to further trade integration between Costa Rica, the US, and other CAFTA-DR countries. Exports to the US began increasing several years before the agreement, but CAFTA-DR accelerated the trend. Costa Rica continues attracting FDI above levels observed in other CAFTA-DR countries, with an increasing share from US investors and a focus on medical devices and business services. Online survey and interviews of high-tech firms in free trade zones found that CAFTA-DR was an important factor in the investment decisions. CAFTA-DR ignited an explosion of changes in the telecom and insurance sectors, bringing new regulatory frameworks, competition, product innovations, and price reductions. Consumers are reaping the benefits of improved telecom and insurance services. But some issues remain for those markets to mature. Finally, the concern regarding the potential negative impact on the Costa Rican Social Security Administration's finances due to the intellectual property rights measures have not been observed.